NUMERICAL OPTIMIZATION OF THE EFP CHARGE BASED ON AN MPB MINE - Dariusz Pyka (Rudarsko-geološko-naftni Zbornik)
This article presents a numerical optimization of an explosively formed charge insert based on an anti-bullet, anti-tank MPB mine (pl. mina przeciwburtowa, eng. anti-side mine). For this purpose, first of all, the chemical composition and microstructure of the currently used EFP inserts and the target material - armour-piercing steel - were analyzed. Then, a series of numerical analyses were carried out, during which not only the material of the EFP insert was changed, but also its thickness, in terms of the most efficient combination, i.e. the initial speed during forming, but also the penetration ability of the insert. The Johnson-Cook constitutive strength model was used to describe the behaviour of materials in the computational environment, and the Jones-Wilkins-Lee model was used to describe the pressure during a detonation. To describe the formation of the EFP charge, SPH particle hydrodynamics was used, which the author had developed in his previous works, thanks to which it was possible to efficiently describe the highly dynamic process. The last element of the research was the validation of numerical models carried out at a military training ground during an experimental study. The results obtained as a result of numerical analyses allowed for the determination of the most optimal combination of material and insert thickness, which indicated future directions of development in order to improve solutions in the field of anti-tank EFP.